Survey: Studies of Tokugawa Economic Thought in the Last Two Decades - Komuro, Masamichi (Annals of the Society for the History of Economic Thought, 2003)
This paper surveys mainly the monograph literature regarding Tokugawa economic thought. Considering what the scholars intend to find through their studies, the present article divides the field into four main groups: (i) A view based on the stage theory of development or the concept of European economic thought. In this category are included two kinds of works which attach much importance to the stage theory based on Western economic development. A group of scholars comment on the backwardness of Tokugawa economic thought as compared with the Western economic thought which was imported after the Meiji restoration. Another group tries to analyse Tokugawa economic thought in terms of such European concepts as mercantilism or physiocracy. Recently, the scholars of this category make use of their theories more flexibly than previously, as a tool to grasp the character of Tokugawa traditions. (ii) A view regarding Tokugawa period as the cradle of Japanese economic growth. The scholars of this category consider that the relatively smooth process of Japanese industrialization was prepared in Tokugawa period. These scholars therefore examine the development of knowledge and thought adequate to the burgeoning market economy of that period. Though they provide some valuable analytical insights into Tokugawa economic thought, some of them might describe the ideas of that period as a too modernised aspect. (iii) A view evaluating Confucian economic thought and a view influenced by the post-modern theories. Some scholars in this category think the modern economic society is reaching its limit and evaluate the harmony between economy and morality in Tokugawa Confucianism. Also represented in this category is work inspired by postmodern theory. This kind of study tries to understand the structure or network of miscellaneous discourses, excluding the modern prejudices. Surely this approach shows the world of the thoughts in a certain period realistically, but it should also consider how to regard the world of this period within the context of chronological history. (iv) An attempt to discover the traditions of economic thought by non-professional thinkers. The scholars of this category find much meaning among the economic thought produced by such non-professional thinkers as samurai-bureaucrats, village masters, intelligent merchants, and so on. These scholars evaluate such non-professional thoughts as having a character of their own, finding new materials concerning this kind of subject. However, most of these attempts have not yet been able to connect such thoughts with the whole body of Tokugawa economic thought. The major publications of each of these categories are critically introduced. The general conclusion is as follows. The divisions that have so characterized the field will be perpetuated in some form. But there is a sense that the very virulent and sterile phase of controversy is spent. Though marked by wide differences in approach and broad diversification of subjects, this field of study is maturing, and the described categories are going to stimulate constructively to one another.